2021
DOI: 10.1186/s12935-021-01778-2
|View full text |Cite
|
Sign up to set email alerts
|

LiCl induces apoptosis via CHOP/NOXA/Mcl-1 axis in human choroidal melanoma cells

Abstract: Background Choroidal melanoma is the most common primary intraocular malignancy that occurs in adults. Lithium Chloride Promotes Apoptosis in Human Leukemia NB4 Cells by Inhibiting Glycogen Synthase Kinase-3 Beta. In this study, we aimed to understand whether LiCl exerts anticancer effects on choroidal melanoma cells and elucidate the underlying molecular mechanisms. Methods Human choroidal melanoma cells were treated with LiCl, and cell survival w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
(38 reference statements)
2
7
0
Order By: Relevance
“…Notably, we discovered that BAY-885-induced ER stress is required for the downregulation of Mcl-1 and the upregulation of Bim, as indicated by the use of an ER stress inhibitor (GSK2656157), and that genetic knockdown of PERK abolished BAY-885ʹs effects on Mcl-1 and Bim expression ( Figure 4d ). In accordance with our findings, many studies found that activation of ER stress caused downregulation of Mcl-1 [ 37–39 ]. Upregulation of Mcl-1 could attenuate the apoptosis induced by ER stress in melanoma cells [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Notably, we discovered that BAY-885-induced ER stress is required for the downregulation of Mcl-1 and the upregulation of Bim, as indicated by the use of an ER stress inhibitor (GSK2656157), and that genetic knockdown of PERK abolished BAY-885ʹs effects on Mcl-1 and Bim expression ( Figure 4d ). In accordance with our findings, many studies found that activation of ER stress caused downregulation of Mcl-1 [ 37–39 ]. Upregulation of Mcl-1 could attenuate the apoptosis induced by ER stress in melanoma cells [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, Noxa gene expression is mediated by ATF3 in Noxa-dependent intrinsic apoptosis, i.e., the ATF3-CHOP/Noxa axis. For example, the CHOP/NOXA/Mcl-1 axis contributes to LiCl-induced apoptosis ( 26 ), and ATF4-triggered Noxa- and DR5-dependent extrinsic apoptosis have been seen in fangchinoline-treated esophageal squamous cells ( 27 ). Because ER stress in BTZ-treated MM cell lines is beyond their self-defense capacity, the MM cell activates apoptotic signals to remove damage organelles ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have shown that bipolar disorder patients receiving lithium therapy have a significant lower risk for cancer than those not treated with lithium [9] , [10] , [11] , [12] . Recent studies have found that lithium salts can inhibit the proliferation and development of various tumors [13] , [14] , [15] , [16] , [17] , [18] . Existing research has demonstrated that lithium exerts most of its pharmacological effects by inhibiting the activity of some phosphate-transfer enzymes, including GSK3β, which require magnesium as a co-factor [19] .…”
Section: Introductionmentioning
confidence: 99%